New diagnosis for Allodaposuchus precedens, the type species of the European Upper Cretaceous clade Allodaposuchidae. Issue 2 (27th May 2019) - Narváez, Iván; Brochu, Christopher A; De Celis, Ane; Codrea, Vlad; Escaso, Fernando; Pérez-García, Adán; Ortega, Francisco
Abstract: Allodaposuchus precedens is a basal member of Eusuchia, which was established almost a century ago on a set of cranial and postcranial fragmentary remains from the lower Maastrichtian of Vălioara, Romania. It was the first described member and type species of Allodaposuchidae, a recently described European clade representing one of the nearest outgroups to Crocodylia. Although our understanding of the group has expanded in recent years through the description of new forms, a review of Al. precedens is needed. The detailed revision of the classical material from Vălioara, including cranial and postcranial remains, and a comparison with the nearly complete skull from the Romanian synchronous locality of Oarda de Jos, allows us to emend the diagnosis for Al. precedens .